Determination of the Phenolic Profile and Antioxidant Activity of Leaves and Fruits of Spanish Quercus coccifera - L. Molina-García; R. Martínez-Expósito; M. L. Fernández-de Córdova; E. J. Llorent-Martínez (Journal of Chemistry)
In this work, we report the phytochemical composition and antioxidant activity of methanol extracts of leaves and fruits (acorns) of Quercus coccifera (kermes oak). Forty-one compounds were characterized using high-performance liquid chromatography with electrospray multistage mass spectrometry (HPLC-ESI-MSn) with an ion trap mass spectrometer. A high percentage of the detected compounds were gallic acid derivatives, although some saccharides and flavonoids were also present. This phytochemical pattern is typical in Quercus species, which are rich in gallotannins. These compounds are partially responsible for the cardioprotective effects observed in different food samples containing them. We evaluated the antioxidant activity by ABTS and DPPH assays. In both cases, high antioxidant activity was observed, being higher in acorns than in leaves. The high antioxidant potential of the extracts, which is related to the high total phenolic content, indicates the potential benefit of the use of this species as a source of bioactive compounds.